2014
DOI: 10.1155/2014/489292
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Relationship between Plasma Reactive Oxygen Metabolites and Periodontal Condition in the Maintenance Phase of Periodontal Treatment

Abstract: Aim. The present cohort study describes the longitudinal relationship between plasma oxidative status and periodontitis progression during the maintenance phase of treatment. Materials and Methods. Forty-five patients (mean age 58.8 years) were monitored from 2008 to 2013. Periodontal conditions, including probing pocket depth (PPD) and clinical attachment level (CAL), were recorded. Measurements of plasma reactive oxygen metabolites (ROM) and biologic antioxidant potential (BAP) were performed to evaluate pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Overwhelming evidence indicates that oxidative stress plays a central role in the periodontal tissue and alveolar bone destruction [ 17 , 18 ]. Indeed, a recent clinical study indicated that an increase in plasma reactive oxygen metabolites (ROM) levels was associated with that in the clinical attachment level in periodontal patients whose plasma ROM level was low [ 19 ].…”
Section: Increase In Oxidative Stress and Lipid Oxidation Caused Bmentioning
confidence: 99%
“…Overwhelming evidence indicates that oxidative stress plays a central role in the periodontal tissue and alveolar bone destruction [ 17 , 18 ]. Indeed, a recent clinical study indicated that an increase in plasma reactive oxygen metabolites (ROM) levels was associated with that in the clinical attachment level in periodontal patients whose plasma ROM level was low [ 19 ].…”
Section: Increase In Oxidative Stress and Lipid Oxidation Caused Bmentioning
confidence: 99%
“…They observed a positive correlation between baseline plasma RM levels and mean an alteration in LCA with mean alteration in the RM levels and bleeding on probing. 21 Significant results were also observed while making an intragroup comparison in relation of meaning GCF resistin levels in both the study groups at different time intervals. In inflammatory conditions such as periodontal infection, expression of resistin by inflammatory cells might be responsible for an increase in increase in resistin levels in patients with chronic periodontitis.…”
Section: Discussionmentioning
confidence: 85%
“…37 Previous study also reported the connection between clinical attachment level with the escalation of reactive oxygen metabolites (ROM). 38 Moreover, mitochondria as the major producer of ROS in cells causes a chronic over production which leads to increased oxidation of LDL in atherosclerosis development. 39 Another study reported that Porphyromonas gingivalis infection might increase the LDL levels and induces hypercholesterolemia.…”
Section: Discussionmentioning
confidence: 99%